Accountable Government in Africa Perspectives from public law and political studies - Chirwa, Danwood; Nijzink, Lia (UCT Press, 2012)
In the early 1990s, a wave of democratisation swept the African continents, resulting in a flurry of constitution-making and constitutional revision. Two decades later, leading experts in the fields of public law, political sciemnce and democratisation studies assess to what extent accountable governance has takenroot in Africa. this book represesents new knowldge about legal and political developments in a number of African countries - Ghana, Malawi, Mali, South Africa, Tanzania, Uganda and Zambia, with further references to Mozambique, Kenya and Swaziland - bringing the policy goal of developing and deepening democratic governance and accountable government on the continent up to date.